2015
DOI: 10.1016/j.jval.2015.03.795
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use And Risk Of Developing Diabetes: A Network Meta-Analysis

Abstract: A137 with maternal hypertension. Early diagnosis and treatment through regular antenatal check-up is a key factor to prevent PIH and its complications. Interventions to improve maternal health through information, education and counselling of women of child bearing age should be implemented.Objectives: Increased perioperative blood pressure (BP) variability in cardiac surgery is associated with negative clinical outcomes and increased health resource utilization (HRU). Clevidipine, an ultrashort-acting, arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Notably, statins increase LPL serum mass and activity in T2D (Endo et al 2004). Perhaps these findings offer some explanation as to why some statins increase, albeit modestly, the risk of T2D (Thakker et al 2016). Together, these studies demonstrate evidence implicating a change in cholesterol metabolism, favoring intracellular cholesterol accumulation, as a potential risk factor for T2D.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Notably, statins increase LPL serum mass and activity in T2D (Endo et al 2004). Perhaps these findings offer some explanation as to why some statins increase, albeit modestly, the risk of T2D (Thakker et al 2016). Together, these studies demonstrate evidence implicating a change in cholesterol metabolism, favoring intracellular cholesterol accumulation, as a potential risk factor for T2D.…”
Section: Discussionmentioning
confidence: 76%
“…As to why lipid lowering drugs, such as statins, are associated with increased incidence of new on-set diabetes remains imperfectly understood, yet mechanisms have been proposed and discussed in the literature (Brault et al 2014;Robinson 2015). Interestingly, nearly two decades of randomized, control trials and meta-analyses have revealed that the risk is not the same among statins with atorvastatin, simvastatin, and rosuvastatin being the most diabetogenic, lovastatin and fluvastatin having an intermediate risk, and pravastatin and pitavastatin having the lowest diabetogenicity (Millan Nunez-Cortes et al 2016;Thakker et al 2016). In fact, basic and clinical data suggest that these least diabetogenic statins, especially pitavastatin, may even exhibit a positive effect on glucose metabolism (Teramoto 2011;Daido et al 2014;Huang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, rosuvastatin was the only statin to independently display a significant increase in the risk of new onset diabetes (pooled OR: 1.18; 95% CI: 1.04-1.33; P = .009; 4 RCTs). 15 However, baseline hemoglobin levels, additional risk factors for the development of diabetes, and risks versus benefits of statin therapy initiation must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis of observational studies reported similar findings (RR 1.44, CI 1.31-1.58; I 2 = 97%) [79] and also described it as a class effect with rosuvastatin and atorvastatin reportedly associated with the highest risk. This was also shown in a network meta-analysis from 2016 (pooled OR 1.12, CI 1.05-1.21; I 2 = 36%) that reported the highest risk with atorvastatin 80 mg (OR 1.34, CI 1.14-1.57), followed by higher and lower doses of rosuvastatin (OR 1.17, CI 1.02-1.35) and simvastatin (OR 1.13, CI 0.99-1.29) [80] (Table 1). A 2011 meta-analysis of 5 statin trials with 32,752 non-diabetic patients reported a greater diabetics incidence associated with intensive statin dose compared to the moderate dose [76].…”
Section: New-onset Diabetes Mellitus (Nod)mentioning
confidence: 99%